ANALISIS REVITALISAI PASAR TERHADAP PENDAPATAN PEDAGANG (STUDI KASUS PADA PEDAGANG PASAR TERPADU DINOYO KOTA MALANG) - dwi muriana; sri nuringwahyu; dadang krisdianto (JIAGABI (Jurnal Ilmu Administrasi Niaga/Bisnis), 2020)
The purpose of this study is to describe market revitalization by looking at physical aspects, economic aspects and social aspects, describe the income of traders related to the income of traders in the Dinoyo Integrated Market in Malang seen from the condition and ability of traders, market conditions, capital and other factors after Revitalization. This study uses primary data and secondary data, data obtained by observation, interview and documentation. This research uses a descriptive method with a qualitative approach. The results of this assessment indicate that revitalization is carried out in accordance with expectations, where the facilities provided add to the sense of comfort, more orderly and increase consumer interest. The income of traders also increased because the frequency of consumers increased towards traditional markets after the revitalization.